National Law Development through Civil Procedure Law Reform as a Manifestation of State Goals during the Covid-19 Pandemic - Al Fikry, Ahmad Habib; Afandi, Muhammad Riyan; Latifiani, Dian (Universitas Negeri Semarang, 2021)
The purposes of this paper are: (i) to describe various problems in the philosophical, sociological and juridical aspects of the existence of civil procedural law as formal law in Indonesia; and (ii) offer solutions to these problems by updating the civil procedural law. The method in this paper uses normative legal research with a statutory approach by conducting a literature study using primary and secondary materials. The results of this paper indicate several things. The first, sociologically, people's lives develop dynamically so that the provisions of civil procedural law are not in accordance with the times. As for juridically, this provision is not unification, legal uncertainty, and a legal vacuum. The second, legal reform is part of the development of national law by taking into account the framework of the national legal system. The third, there are efforts and forms of civil procedural law reform carried out by each element of state power. The novelty of this paper is containing a comprehensive discourse that answers the problem of the applicability of civil procedural law with the efforts and forms of reform of civil procedural law in Indonesia. The conclusion in this paper is the provisions of civil procedural law need to be updated based on philosophical, sociological, and juridical considerations. Reform of civil procedural law must take into account the national legal system, principles, and content material in its formation.